Key candidate genes for male sterility in peppers unveiled via transcriptomic and proteomic analyses - Yang, Shimei; Luo, Xirong; Jin, Jing; Guo, Ya; Zhang, Lincheng; Li, Jing; Tong, Shuoqiu; Luo, Yin; Li, Tangyan; Chen, Xiaocui; Wu, Yongjun; Qin, Cheng (Frontiers in Plant Science, 2024)
This study aimed to enhance the use of male sterility in pepper to select superior hybrid generations. Transcriptomic and proteomic analyses of fertile line 1933A and nucleic male sterility line 1933B of Capsicum annuum L. were performed to identify male sterility-related proteins and genes. We identified 2,357 differentially expressed genes, with 1,145 and 229 enriched in Gene Ontology and Kyoto Encyclopedia of Genes and Genomes databases, respectively. Through proteomics and association analyses, 7,628 quantifiable proteins were identified in the nucleic male sterility and fertile lines. Among these, 29 significant proteins and genes were identified. Notably, two CaPRX genes were identified via proteomics, five CaPRX genes were identified via transcriptomics, and three CaPRX genes were identified via association analysis, thus highlighting the significance of CaPRX genes in the nucleic male sterility line and fertile line pepper. A comprehensive analysis of the whole genome of peppers was conducted, including phylogenetic trees, physical and chemical properties, gene structural features, collinearity, and expression characteristics. In total, 66 CaPRX genes were identified in pepper, which were categorized into 13 subfamilies, all of which contained typical conserved domains of CaPRX genes and were unevenly distributed on 12 chromosomes (including the virtual chromosome Chr00). Meanwhile, the results indicated that male sterilityrelated genes were expressed at different degrees under salt stress. Coexpression network analysis revealed that multiple transcription factors were coexpressed with CaPRXs, indicating their involvement in inducing salt stress in peppers. The study findings provide a theoretical foundation for genetic breeding by identifying genes, metabolic pathways, and molecular mechanisms involved in male sterility in pepper.